Public Relations and the Christian Moral - Kovács Halay, István János (2012)
The Public Relationship makes up an area of the communication sciences wherethe moral and Christian values are important in its development. All the social organizationsthat can be privates or public should keep the good relationship amongits members, which must be based in the truth, the honesty, and the respect for thehuman dignity. No one organization can reach its development based in negativeactions that can be very harmful for its members. The human relationship mustdevelopment together to the society following the commandment that our ChristLord taught us: “Love your neighbor as yourself.” Here is stressed the importanceof the faith, the forgiven, the honesty, the truth, the fellowship and other moral values.These are as a fundamental column